PELAKSANAAN KEBIJAKAN OBAT GENERIK DI APOTEK KABUPATEN PELALAWAN PROVINSI RIAU - Aini Suryani; Mubasysyir Hasanbasri; Nunung Priyatni (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Medicine is an integral part of community healthservice. Therefore it must be available in sufficient quantity,types and adeqaute quality, properly distributed and accessiblefor community when its needed. In order to meet thecommunity’s need for medicine and to guarantee medicineaccessibility, the government released generic medicine policy.Although the price of the generic medicine has already beenset up and fixed by government, there are variety of the pricestill can be found on implementation of the generic medicinesold in the pharmacy store or in the market, and can causeprice uncertainty for community in finding medicine they need.That is why a research needs to be conduct towardimplementation of the generic medicine price policy on thedistribution channel especially at the pharmacy store.onPelalawan District in Riau Province.Method: This research is non experimental/observationalresearch with qualitative and quantitative method using crosssectional design, data analyzed descriptively.Result: Research result indicates that access to genericmedicine at pharmacy store for available medicine are 99,3%,for un available medicine are 0,7% and for replaced medicineare 0,5%. Average availability of the medicine at the pharmacystore are 4-7,3 months. Highest availability rate for medicine isHidrocortison cream 2,5% for 7,3 months and the lowest isPirazinamid tablet 500 mg for 4 months. Pharmacy store thathave an expired medicine are PR (0,7%) and KH (2%). Everypharmacy store have no damaged medicine, 0% percentage.Almost all pharmacy store experiencing out of supply formedicine between 4 to 90 days. Price of the medicine soldaveragely increasing from its pharmacy store Highest RetailPrice (HRP). But there are several medicine that sold under theHRP The highest price medicine that are sold higher than itsHRP is Clorfeniramin Maleat (CTM) tablet by 515,4% increaseand Dexametason tablet is the lowest price sold under HRP by65,2%. Even so they are Alopurinol, Digoksin, and Ranitidin.From in depth interviews with patients, can be learn that theyhave a purchase ability for generic medicine.Conclusion: Implementation of generic drug price on Pelalawandistrict is good. It can be seen from generic medicine accessby community that are high after the release of regulation fromHealth Department of Republic Indonesia, the level of availabilityof generic medicine on pharmacy store at Pelalawan Districtare low but there are no expired or damaged medicine. Theprice of generic medicine at Pelalawan District are variable butthe community still can afford to buy them.Keyword: Generic medicine, availability and affordability.